Noise from the traffic volume of motorcycle during the Covid-19 pandemic: A case study of Wiyata Mandala Junior High Schoool Bogor - Syaiful Syaiful; Hermanto Siregar; Ernan Rustiadi; Eri Susanto Hariyadi; Muhammad Nanang Prayudyanto; Rulhendri Rulhendri (Sustinere: Journal of Environment and Sustainability, 2022)
Each motor vehicle produces a variety of noise. For areas which directly intersects the highway this noise has a considerable impact. The volume of motorcycles and private as well as public vehicles all have a significant effect on noise. From all analytical calculations, the largest equation was obtained one the second day of research on the second point of Sound Level Meter 2 (SLM2). The calculation is that y = 0,0158x – 1,0176. This equation indicates that if there is no decrease in the volume of the motorcycle, the noise level on the SLM2 is 65.21 dBA. If there is an increase or decrease in the volume of a motorcycle, it will have a significant effect on noise. The second largest equation was obtained on the second day of the research at the third point from the Sound Level Meter 3 (SLM3) and the calculation of the equation is y = 0,01 – 6,074. The purpose of the above equation is that if there is an increase in the volume of a motorcycle, the noise on the SLM3 is 60.840 dBA. According to the findings, there was a reduction in the number of motorcycles during the Covid-19 pandemic, because schools were closed and students did not attend school.